Transforming harmful representations, investigating violence and empowering care practises in masculinities - Moura, Tatiana (Frontiers in Sociology, 2024)
Stemming from a critical perspective of feminist studies on masculinities, this article proposes to explore how dominant and hegemonic masculinities are being reimagined, renegotiated and reconstructed, by understanding new patterns of violence amongst boys, on the one hand; and how care, as the opposite of violence, and a concept in construction from a feminist perspective, can be adopted, put in practise and understood. From a feminist standpoint masculinities studies need to go through a renewed problematisation of the social constructions of masculinities in a space–time context that intersects the economic crisis, health crisis and, on the other hand, implementation of legislation and initiatives for gender equality and citizenship, and is marked by social challenges that are related to the increase of gender inequality, violence indicators and extremism but also the emergence of caring masculinities that need closer attention. This feminist approach to masculinities allows us to critically challenge hegemonic models of boyhood/manhood, specifically by developing a FEMINIST THEORY OF CARING MASCULINITIES. Through a critical understanding of the new patterns and ways in which patriarchal masculinities are perpetuated in society, and placing CARE as the centrepiece and pro-active practise that opposes violence sustained models of masculinities, feminist masculinities studies can challenge dominant forms of masculinity by taking action in diverse social contexts and emphasising empathy, emotional expression, and cooperative relationships.